Pengaruh Harga, Promosi, Citra Merek, dan Kualitas Produk terhadap Kepuasan Konsumen pada Klinik Kecantikan Emdee Easy di Batam - Lucky Anggia Chairunisah Sipahutar; Sabri Sabri; Nurmayunita Nurmayunita (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This research is motivated by the phenomenon of decreasing number of customers at Emdee Easy Beauty Clinic Batam, which indicates the need for an evaluation of marketing strategies. The purpose of this study is to analyze the influence of price, promotion, brand image, and product quality on consumer satisfaction. The research method used is quantitative associative with a sample of 91 respondents taken using simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that simultaneously, price, promotion, brand image, and product quality had a significant effect on consumer satisfaction (F count 14.111 > F table 2.47). Partially, the variables of price, promotion, and brand image have a positive and significant influence, but product quality does not have a significant effect on consumer satisfaction in this study. The implication of these findings is that clinic management needs to prioritize competitive pricing strategies, strengthen promotional activities, and maintain a positive brand image to sustain and increase customer satisfaction.